2020
DOI: 10.1159/000511658
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of Dickkopf-Related Protein 1 Decrease as Measured GFR Declines and Are Associated with PTH Levels

Abstract: <b><i>Background:</i></b> The Wnt/β-catenin pathway has been implicated in the development of adynamic bone disease in early-stage chronic kidney disease (CKD). Dickkopf-related protein 1 (DKK1) and sclerostin are antagonists of the Wnt/β-catenin pathway yet have not been widely used as clinical indicators of bone disease. This study characterized levels of DKK1, sclerostin, and other biomarkers of mineral metabolism in participants across a spectrum of inulin-measured glomerular filtra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This is in line with the loss of correlation between serum and osseous sclerostin in corticosteroid-treated patients in our previous report [ 44 ]. Moreover, since it has been reported that serum sclerostin levels highly depend on renal function [ 25 , 45 ], our lack of correlation could, at least to a certain extent, be explained by the fact that eGFR levels in the high turnover group were considerably higher than in low and normal turnover patients. Hence, the expected lower serum sclerostin levels in the high turnover group could be confounded by more pronounced renal retention.…”
Section: Discussionmentioning
confidence: 83%
“…This is in line with the loss of correlation between serum and osseous sclerostin in corticosteroid-treated patients in our previous report [ 44 ]. Moreover, since it has been reported that serum sclerostin levels highly depend on renal function [ 25 , 45 ], our lack of correlation could, at least to a certain extent, be explained by the fact that eGFR levels in the high turnover group were considerably higher than in low and normal turnover patients. Hence, the expected lower serum sclerostin levels in the high turnover group could be confounded by more pronounced renal retention.…”
Section: Discussionmentioning
confidence: 83%
“…Alongside Dkk1, sclerostin displays increased circulating levels in CKD patients, although there is vast variance across the analyzed groups [83,[87][88][89][90]. Contrasting with Dkk1, sclerostin shows an increasing trend with a decline of eGFR, independent of PTH levels [83]. However, assessment of the effect bared by PTH alone on sclerostin returned dissimilar results to the ones observed in CKD.…”
Section: Sclerostin Regulation-downstream Cascades In Pth Signaling M...mentioning
confidence: 88%
“…Dkk1 levels increase early in the course of the disease, mainly under the stimulus of tubular epithelial proliferation. With advancing disease, as measured through eGFR, Dkk1 circulating levels progressively decline but never return to the normal range [82,83]. More importantly, the extent of Dkk1 concentration decline is independently and inversely associated with PTH levels in CKD subjects.…”
Section: Dkk1 As An Intermediate Marker Of Pth Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…The Wnt/β-catenin pathway has been implicated in developing adynamic bone disease in early-stage chronic kidney disease (CKD). Dickkopf-related protein 1 (DKK1) and sclerostin are antagonists of the Wnt/β-catenin pathway yet have not been widely used as clinical indicators of bone disease [3].…”
Section: Introductionmentioning
confidence: 99%